PALEOMAGNETIC ANALYSIS OF THE FLYNN CREEK AND WELLS CREEK IMPACT STRUCTURES, TENNESSEE, U.S.A. - Rohleder, Nicholas (My University, 2019)
The Flynn Creek impact structure consists of a 3.8-km circular feature that contains deformed Ordovician through Devonian limestones and dolomites. The age of this structure is stratigraphically constrained by the Ordovician Knox Group and the overlying undeformed late Devonian through Mississippian Chattanooga Shale. Paleomagnetic samples were collected from deformed Flynn Creek Breccia, a fallback breccia from the inside of the structure. Stepwise thermal demagnetization and alternating field demagnetization of tilted limestone samples reveals a characteristic remanent magnetization (ChRM) with southeasterly declinations and moderate down inclinations, with maximum unblocking temperatures of 440°C—the ChRM resides in magnetite. The calculated pole position is 36.7°N, 131.3°E (dp = 5.8°, dm = 11.5°) which lies on the late Carboniferous to early Permian portion of the apparent polar wander path (APWP) for North America. The Wells Creek impact structure consists of a 12-km circular feature that contains deformed Ordovician through Mississippian limestones and dolomites. The age of this structure is stratigraphically constrained by the Ordovician Knox Group and the overlaying undeformed Cretaceous Tuscaloosa Gravel (200Ma +/- 100Ma). Paleomagnetic samples were collected from deformed Fort Payne Limestone and Warsaw Limestone, fallback breccias from the southern rim of the structure. Stepwise thermal demagnetization and alternating field demagnetization of tilted limestone samples reveals a ChRM with southeasterly declinations and moderate down inclinations (declination = 152°, inclination = 18.5°, k = 105.7, and a95 = 6.5), with maximum unblocking temperatures of 440°C—the ChRM resides in magnetite. The pole lies at 37.1°N, 127.9°E (dp = 3.5°, dm = 6.8°) which lies on the late Carboniferous to early Permian portion of the apparent polar wander path (APWP) for North America. The ChRM that resides in both of these structures was imparted from the same origin and is the result of a regional remagnetization event associated with the Alleghenian Orogeny. The age of the Flynn Creek impact structure was not further constrained through paleomagnetic tests; although the Wells Creek impact structure now has an upper constraint at the late Carboniferous to early Permian. The ChRM is interpreted as a chemical remanent magnetization (CRM) imparted by the influx of heated orogenic brines into these structures and is carried in secondary magnetite formed by alteration of pyrite. Although there are other possible mechanisms for remagnetization, the lack of deep burial and evidence of alteration in petrographic study indicate that this magnetization was the result of hydrothermal fluid activity.
Keywords: Geology; Paleomagnetism; Impact Crater